(untitled) (Physical Education, Health and Social Sciences, 2025)
The present study aims at the analysis of the novel The Writing on my Forehead (2009) by Nafisa Haji by applying Marxist-Feminist theory. It delineates the idea that women are doubly oppressed on the basis of their gender as well as on the basis of their economic status. This research also propounds that it is possible to come out or emancipate from this oppressed and suppressed plight by removing the causes of their subjugation. One of the prime causes of women’s subjugation is the lack of opportunities to earn. Furthermore, they are also not allowed to own any means of production. Men in the role of husbands subjugate their wives and torture them emotionally as well as physically. They themselves indulge in extra-marital and sexual relationships but expect their wives to be faithful and loyal to them. The source text is analyzed to find out how the chosen novel conforms to Marxist-Feminist theory and it was found that oppression of women in their own families is largely the result of the patriarchal set up of the family. The result seems to conclude that along with patriarchy, economic conditions are a significant determining element in shaping the social roles of human beings particularly women. Women undergo miseries both at the hands of patriarchy and capitalism. If women are empowered economically they would get acceptance as fruitful members of society. The researcher has employed close reading technique to prove her point. The qualitative method of research has been used as this method provides every minute detail and in depth analysis of the text under consideration by applying close text reading technique. Instances from the original text i.e. The Writing on my Forehead are taken and analyzed qualitatively.